Novel biomarkers with potential for cardiovascular risk reclassification. (19th May 2017) - Mallikethi-Reddy, Sagar; Briasoulis, Alexandros; Akintoye, Emmanuel; Afonso, Luis
Abstract: Precise estimation of the absolute risk for CVD events is necessary when making treatment recommendations for patients. A number of multivariate risk models have been developed for estimation of cardiovascular risk in asymptomatic individuals based upon assessment of multiple variables. Due to the inherent limitation of risk models, several novel risk markers including serum biomarkers have been studied in an attempt to improve the cardiovascular risk prediction above and beyond the established risk factors. In this review, we discuss the role of underappreciated biomarkers such as red cell distribution width (RDW), cystatin C (cysC), and homocysteine (Hcy) as well as imaging biomarkers in cardiovascular risk reclassification, and highlight their utility as additional source of information in patients with intermediate risk.